Middle Maghreb field and population Between the 4th and 6th centuries AH, 10th and 12th centuries AD - benamier, zohir; bekkaye, houaria (Journal of Social Sciences and Humanities, 2022)
Through this study, we review the geographical area of the State of Beni Hammad, which has experienced fluctuations in the borders with its neighboring countries, due to the nature of political relations, as well as repeated military confrontations, the strength of the state at times was a key factor in maintaining its borders, which were expanding and shrinking according to the circumstances and political variables surrounding it, including most of the territory of the Middle Maghreb islamic in the Middle Ages, we find the Sanhadja tribe and its branches that controlled the territory of the Middle Maghreb and were credited with establishing a political entity and resurrecting the state project, and some of the other countries, Other Berber tribes, in addition to the various human elements that coexisted among themselves and formed the Hammadi society, had a role in preserving the general framework of the state's borders throughout their existence, despite differences in gender, race or even creed, which resulted in the convergence of ideas, followed by a boom in urbanization, life, science, intellectual and economic, which was reflected in the civilized sophistication reached by the State of Bani Hammad in the Middle Ages. Keywords: Society, Middle Maghreb, Asher, Mount Oras, Tribe, Sanhadja. Résumé: Grâce à cette étude, nous passons en revue la zone géographique de l’État de Beni Hammad, qui a connu des fluctuations dans les frontières avec ses pays voisins, en raison de la nature des relations politiques, ainsi que des confrontations militaires répétées, la force de l’État a parfois été un facteur clé dans le maintien de ses frontières, qui ont été en expansion et en diminution en fonction des circonstances et des variables politiques qui l’entourent, y compris la plupart du territoire du Maghreb central islamique au Moyen Age, nous trouvons la tribu Sanhadja et ses branches qui contrôlaient le territoire du Maghreb central et ont été crédités d’établir une entité politique et de ressusciter le projet d’État, et certains des autres pays, D’autres tribus berbères, en plus des divers éléments humains qui coexistaient entre elles et formaient la société Hammadite, ont joué un rôle dans la préservation du cadre général des frontières de l’État tout au long de leur existence, malgré les différences de genre, de race ou même de croyance, qui ont abouti à la convergence des idées, suivie d’un boom de l’urbanisation, de la vie, de la science, intellectuelle et économique, qui s’est reflété dans la sophistication civilisée atteinte par l’État de Bani Hammad au Moyen Age. Mots clés : Société, Maghreb central, Asher, Mont Oras, Tribu, Sanhadja.